Macrophthalmus graeffei A. Milne Edwards, 1873 (Crustacea: Brachyura: Macrophthalmidae): a new Indo-Pacific guest off Rhodes Island (SE Aegean Sea, Greece) - PANCUCCI-PAPADOPOULOU, M.A.; CORSINI-FOKA, M.; NALETAKI, M. (Mediterranean Marine Science, 2010)
A new alien crab, the macrophthalmid Macrophthalmus graeffei, is reported from the eastern coastline of Rhodes Island. The species, of Indo-West Pacific origin, is known from muddy sediments up to about 80 m depth. In the Mediterranean, its presence has been observed along Levantine coasts as well as along the Turkish coast of the Aegean Sea.Macrophthalmus graeffei increases to twelve the number of alien brachyurans present in the Hellenic SE Aegean Sea, ten of them having Indo-Pacific origin.